Kajian Tenaga Kerja Milenial di Bidang Hospitaliti - Ni Gusti Made Kerti Utami; Dede Kuswandi; Erfin Roesfian; Maksum Suparman; Lien Maulina; Asdiansyah Saputra (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2020)
Millennial generation or generation Y is "the generation born in 1980 to 1995" (Kemenppa, 2018: 15) with an estimated age of 23 years to 38 years. Currently, the workforce almost dominated by the millennial workforce. Millennials are very familiar with the use of electronic-based information technology, so this generation is considered an asset in the company because of the ability to use information technology. The facts that are extracted from this research are regarding the ability to use technology, the ease of getting a job, the level of loyalty and mastery of competence in the field of work. The approach used is a qualitative approach to determine the assessment of millennial workforce in the hospitality sector. Based on the results of the analysis, it is known that the ability to use technology makes it easy for millineal workers to get new jobs with poor loyalty with good competency skills resulting in high employee turnover in companies in the field of hospitality.